A case study on the stability of a big underground powerhouse cavern cut by an interlayer shear zone in the China Baihetan hydropower plant - Lifang Zou; Guotao Meng; Jiayao Wu; Wei Fu; Weijiang Chu; Weiya Xu (Deep Underground Science and Engineering)
Abstract The big underground powerhouse cavern of the China Baihetan hydropower plant is 438 m long, 34 m wide, and 88.7 m high. It is cut by a weak interlayer shear zone and its high sidewall poses a huge stability problem. This paper reports our successful solution of this problem through numerical simulations and a replacement‐tunnel scheme in the detailed design stage and close site monitoring in the excavation stage. Particularly, in the detail design stage, mechanical parameters of the shear zone were carefully determined through laboratory experiments and site tests. Then, deformation of the surrounding rocks and the shear zone under high in situ stress conditions was predicted using 3 Dimensional Distinct Element Code (3DEC). Subsequently, a replacement‐tunnel scheme was proposed for the treatment on the shear zone to prevent severe unloading relaxation of surrounding rocks. In the construction period, excavation responses were closely monitored on deformations of surrounding rocks and the shear zone. The effect of local cracking in the replacement tunnels on sidewall stability was evaluated using the strength reduction method. These monitoring results were compared with the predicted numerical simulation in the detailed design stage. It is found that the shear zone greatly modified the deformation mode of the cavern surrounding rocks. Without any treatment, rock mass deformation on the downstream sidewall was larger than 125 mm and the shearing deformation of the shear zone was 60–70 mm. These preset replacement tunnels can reduce not only the unloading and relaxation of rock masses but also the maximum shearing deformation of the shear zone by 10–20 mm. The predictions by numerical simulation were in good agreement with the monitoring results. The proposed tunnel‐replacement scheme can not only restrain the shear zone deformation but also enhance the safety of surrounding rocks and concrete tunnels. This design procedure offers a good reference for interaction between a big underground cavern and a weak layer zone in the future.